Conceptual Model Of Retaining Expert Knowledge And Its Application In The IT Industry - Mohammad Radzi, Anwar (2006)
The objective of this project is to investigate the use of an automated technique of categorization once knowledge has been acquired thus removing the need for human intervention during the categorization process. A study of various forms of categorizing techniques id first discussed and evaluated and the adopted technique eventually described. A model based on the selected technique is constructed and a prototype scenario to evaluate its feasibility is demonstrated. The proposed technique is expected to offer a viable alternative into the area of knowledge acquisition and retention.